Efektivitas Ekstrak Akar Tuba (Derris elliptica) sebagai Bioinsektisida Ulat Kantung (Metisa plana) di Perkebunan Kelapa Sawit - Jojon Soesatrijo (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Metisa plana is a pests that damage palm oil, which must be controlled because it can reduce the production of palm oil plantation. This research purpose to determine the benefit of tubal root extract as bioinsecticide for Metisa plana in the palm oil plantation. The research was conducted on January to April, 2017. The research was carried out at the Afdeling Alfa Nanuah Estate, PT Tanjung Sawit Abadi, Lamandau District, Central Kalimantan Province. The research was conducted using CRD one factor for mortality and time parameters. The treatment in the research was in the form of tubal root bioinsecticide application with three treatments, ie: A1 5 gr/100 ml of aquades; A2 10 gr/100 ml of aquades; and A3 15 gr/100 aquades. Each treatment was repeated three times so that there were nine experimental samples, while for toxicity parameters using a descriptive analysis design. The result showed that control using tubal root extract as a bioinsecticide of Metisa plana was more effective by using 15 gr/100 ml of aquades with a mortality time of five minutes and the number of Metisa plana that died 10 from each sample.